Novel fluorine-18 labeled 5-(1-pyrrolidinylsulfonyl)-7-azaisatin derivatives as potential PET tracers for in vivo imaging of activated caspases in apoptosis. Issue 17 (1st September 2015) - Waldmann, Christopher M.; Hermann, Sven; Faust, Andreas; Riemann, Burkhard; Schober, Otmar; Schäfers, Michael; Haufe, Günter; Kopka, Klaus
Graphical abstract: Abstract: The programmed type I cell death, defined as apoptosis, is induced by complex regulated signaling pathways that trigger the intracellular activation of executioner caspases-3, -6 and -7. Once activated, these enzymes initiate cellular death through cleavage of proteins which are responsible for DNA repair, signaling and cell maintenance. Several radiofluorinated inhibitors of caspases-3 and -7, comprising a moderate lipophilic 5-(1-pyrrolidinylsulfonyl)isatin lead structure, are currently being investigated for imaging apoptosis in vivo by us and others. The purpose of this study was to increase the intrinsic hydrophilicity of the aforementioned lead structure to alter the pharmacokinetic behavior of the resulting caspase-3 and -7 targeted radiotracer. Therefore, fluorinated and non-fluorinated derivatives of 5-(1-pyrrolidinylsulfonyl)-7-azaisatin were synthesized and tested for their inhibitory properties against recombinant caspases-3 and -7. Fluorine-18 has been introduced by copper(I)-catalyzed azide–alkyne cycloaddition (CuAAC) of an alkyne precursor with 2-[ 18 F]fluoroethylazide. Using dynamic micro-PET biodistribution studies in vivo the kinetic behavior of one promising PET-compatible 5-pyrrolidinylsulfonyl 7-azaisatin derivative has been compared to a previously described isatin based radiotracer.